Demographic and Clinical Profile of Gingival Oral Lichen Planus in a Group of Thai Individuals - Daroonpan, Pissacha; Kaomongkolgit, Ruchadaporn; Tantanapornkul, Weeraya; Palasuk, Jadesada (Journal of Dentistry Indonesia, 2020)
Objective: This study aimed to determine the clinical profile of the gingival lesions of oral lichen planus (OLP) in a group of Thai patients. Methods: The dental records of 67 patients were reviewed. Results: In this study, 51 (76.1%) women and 16 (23.9%) men with a female-to-male ratio of 3.2:1 were included. The average age of patients with OLP was 56.0 ± 12.5 years (ranged = 20–81 years). Furthermore, 52 (77.6%) patients had a history of systemic diseases, and hypertension was predominant. All the patients presented with symptomatic OLP. Multiple OLP lesions were observed in 56 (83.6%) individuals, and single gingival OLP was found in 11 (16.4%) individuals. Among these lesions, 38.8% of reticular and atrophic forms of gingival OLP were primarily detected. Mixed and single clinical forms of gingival OLP were found in 37 (55.2%) and 30 (44.8%) patients, respectively. None of the patients had a family history of OLP, extraoral involvement, or malignant transformation. In addition, 64 (95.5%) patients with gingival OLP were treated with topical steroid, and only 1 (1.5%) patient was treated with a combination of topical and systemic steroids. Conclusion: This study provided information beneficial to OLP diagnosis by general dental practitioners and specialists during a routine oral examination.